Pengaruh Big Data Analytics (BDA) dan Time Pressure terhadap Efektivitas Deteksi Fraud dengan Peran Moderasi Computer Assisted Audit Techniques (CAATs) pada Kantor Akuntan Publik di Jakarta - Michael Fedrix Ericho; Susanto Salim (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of big data analytics and time pressure on the effectiveness of fraud detection and the moderating role of CAATs in Public Accounting Firms in Jakarta. An explanatory quantitative approach using PLS-SEM, data were obtained through a survey of external auditors experienced in computer-based audit technology. The results show that big data analytics significantly increases the effectiveness of fraud detection, however, time pressure significantly decreases the effectiveness of fraud detection. CAATs can act as a moderating influence between big data analytics and the effectiveness of fraud detection significantly. However, CAATs do not moderate the influence between time pressure and the effectiveness of fraud detection. These findings emphasize the importance of technology adoption in improving audit quality